Collaborative Care In Emergency Nursing: Working Together For Timely And Effective Patient Management (Journal of Namibian Studies : History Politics Culture, 2022)
Background: nursing collaborative care in emergency settings plays a crucial role in ensuring timely and effective patient management. This review explores the importance of collaboration among healthcare professionals in emergency situations to provide high-quality care to patients. The key components of nursing collaborative care, including communication, teamwork, and coordination, are essential for delivering timely interventions and improving patient outcomes. By working together and utilizing their unique skills and expertise, nurses can enhance the efficiency of emergency care delivery and promote a patient-centered approach. Aim: to highlights and explore the significance of collaborative care in emergency settings for timely and effective patient management. Design: A systematic review was conducted, from fourteen studies were included. Result: studies demonstrating improved timely and patient effective management more often incorporated inter-professional teamwork than studies that incorporated inter-professional coordination and collaborative care in emergency nursing setting had a positive effect on timely and patient effective management.